You’re Not Hardcore Unless You Live Hardcore (KULT_online, 2022)
In Generation Reagan Youth, Robert Winkler combines Rahel Jaeggi’s Critique of Forms of Life (2018) with whiteness studies and new historicism. He uses these to contextualize the U.S. hardcore punk scene’s stances on neoliberalism and its key concepts from the emergence of first-generation hardcore in the 1970s through the 1990s. Winkler not only constructs one concept of what hardcore is but points out the diversification of the scene to include countermovements such as Riot Grrrl, Queercore, and Latino Punk, providing a compelling read to scholars and hardcore kids.